2019
DOI: 10.3390/en12061094
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Natural Gas Spot Price Forecasting with Least Squares Regression Boosting Algorithm

Abstract: Natural gas is often described as the cleanest fossil fuel. The consumption of natural gas is increasing rapidly. Accurate prediction of natural gas spot prices would significantly benefit energy management, economic development, and environmental conservation. In this study, the least squares regression boosting (LSBoost) algorithm was used for forecasting natural gas spot prices. LSBoost can fit regression ensembles well by minimizing the mean squared error. Henry Hub natural gas spot prices were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…Despite this fact, no detailed analysis of the forecasting performances these similar models have been applied in the natural gas markets. Most of studies being conducted for natural gas price forecasting rely heavily on the artificial neural network approaches (MacAvoy and Moshkin, 2000;Buchananan et al, 2001;Nguyen and Nabney, 2010;Abrishami and Varahrami, 2011;Azadeh et al, 2012;Busse et al, 2012;Salehnia et al, 2013;Mishra and Smyth, 2016;Čeperić et al, 2017;Su et al, 2019). Therefore, the existence of structural instability, which is documented in more recent studies, is likely to be overlooked in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this fact, no detailed analysis of the forecasting performances these similar models have been applied in the natural gas markets. Most of studies being conducted for natural gas price forecasting rely heavily on the artificial neural network approaches (MacAvoy and Moshkin, 2000;Buchananan et al, 2001;Nguyen and Nabney, 2010;Abrishami and Varahrami, 2011;Azadeh et al, 2012;Busse et al, 2012;Salehnia et al, 2013;Mishra and Smyth, 2016;Čeperić et al, 2017;Su et al, 2019). Therefore, the existence of structural instability, which is documented in more recent studies, is likely to be overlooked in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical results showed that it effectively improved the short-term price forecasting accuracy compared with other listed models. Su et al [44] proposed the least squares regression boosting (LSBoost) algorithm to forecast the natural gas spot prices. The empirical results revealed that this method had a superior prediction performance.…”
Section: Introductionmentioning
confidence: 99%
“…One such technique, which has been gaining high popularity in recent years, is support vector regression (SVR). In particular, SVR and SVR-based hybrid models have been applied in many studies to forecast prices of energy commodities, including: crude oil (e.g., [13][14][15][16][17][18]) and natural gas (e.g., [19,20]). However, they have been used only by Zhang and Zhang [8] to forecast volatility of energy commodities, specifically crude oil.…”
Section: Introductionmentioning
confidence: 99%